Heavy metals in fluvial sediments of the Odra River flood plains - introductory research - Ibragimow, Aleksandra; Głosińska, Grażyna; Siepak, Marcin; Walna, Barbara (Quaestiones Geographicae, 2010)
The article presents the results of research on concentrations of heavy metals (Cd, Cr, Cu, Ni, Pb and Zn) in fluvial sediment samples collected in the flood plains of the Odra River. The samples were collected from the presently flooded area and from the area which was formerly flooded. The extraction of sediment samples was conducted using aqua regia and four other extractants: 0.01M CaCl2, 0.1M HCl, 0.005M DTPA and 0.02M EDTA. The analysis of the results revealed different concentration values for particular sample collection sites situated along the course of the Odra River. The differentiation of metal concentrations in the investigated samples depending on the extractants was also observed. The concentrations of metals were determined using the technique of atomic absorption spectrometry with flame atomization (F-AAS).